2011
DOI: 10.1093/brain/awr259
|View full text |Cite
|
Sign up to set email alerts
|

The balance between cognitive reserve and brain imaging biomarkers of cerebrovascular and Alzheimer's diseases

Abstract: The cognitive reserve hypothesis explains the disparity between clinical and pathological phenotypes and why, in two individuals with the same extent of neuropathology, one may be demented while the other remains cognitively intact. We examined the balance between brain magnetic resonance imaging measures of the two most common pathologies associated with brain ageing, cerebrovascular disease and Alzheimer's disease, and parameters of cerebral reserve in well-characterized participants born in 1936, for whom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 47 publications
3
76
1
10
Order By: Relevance
“…Recently, there has been increasing interest in the factors that could contribute to individual differences in cognitive and cerebral aging. In particular, there is evidence that cognitive decline is attenuated in elderly people with high levels of intelligence, education, literacy, and occupational attainment (Albert et al, 1995;Christensen, 2001;Manly, Schupf, Tang, & Stern, 2005;Murray et al, 2011). The idea that individuals with stimulating lifetime experience can cope better than others with age-related neural changes and thus minimize cognitive decline has been formalized in the cognitive reserve hypothesis (Steffener & Stern, 2012;Stern, 2002Stern, , 2006Stern, , 2009Tucker & Stern, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing interest in the factors that could contribute to individual differences in cognitive and cerebral aging. In particular, there is evidence that cognitive decline is attenuated in elderly people with high levels of intelligence, education, literacy, and occupational attainment (Albert et al, 1995;Christensen, 2001;Manly, Schupf, Tang, & Stern, 2005;Murray et al, 2011). The idea that individuals with stimulating lifetime experience can cope better than others with age-related neural changes and thus minimize cognitive decline has been formalized in the cognitive reserve hypothesis (Steffener & Stern, 2012;Stern, 2002Stern, , 2006Stern, , 2009Tucker & Stern, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are often referred to as the theory of cognitive reserve which proposes that greater brain integrity can protect the brain from negative neurological sequela through both 'active' and 'passive' pathways [67]. While passive cognitive reserve relates to histology and brain size, active reserve refers to the ability of redundant pathways to take over following damage to the brain [67].…”
Section: (2) Brain Integrity and Cognitive Reservementioning
confidence: 99%
“…This pattern has been observed across a wide range of brain pathologies, including moderate to severe traumatic brain injury [9], cerebrovascular disease [10], hepatitis C [11], and AD [12]. Overall, a strong body of research has found support that intellectual ability, education, and occupational attainment are associated with cognitive reserve [7,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 90%